Identification of Aspergillus cryptic species in hospital environment - Sabino, Raquel (2017)
Selected hospital wards, housing patients at higher risk to develop invasive fungal infections, were screened in order to understand the epidemiology and distribution of Aspergillus, especially regarding the presence of cryptic species.Aspergillus species were identified by b-tubulin and calmodulin sequencing, and a high percentage of cryptic species (i.e., not sensu stricto) was found (59%). Sections Usti, Versicolores and Circumdati harbored the highest proportion of cryptic species [100% (4/4), 95% (19/20) and 90% (9/10), respectively].The high number of cryptic species found raises concerns about the possible reduced susceptibility to antifungals of hospital environmental Aspergillus isolates. These data reinforce the importance of hospital air and surface monitoring, mainly in immunocompromised patients’ wards.